Cause Related Marketing - Pandey, Devendra Prasad (Indian Journal of Marketing, 2007)
"Cause related marketing is the action through which a company, a non-profit organization, or a similar entity markets on image, a product, a service, or a message for mutual benefit (of the entity and the cause)"1 Cause-related marketing gives the value of brand image, corporate reputation, satisfaction etc. Social investors stands to gain from a better understanding of cause marketing because that understanding could help them better evaluate whether that company is doing an effective job in differentiating itself. Cause-related marketing (CRM) is marketing strategy-linking purchases of a product with fundraising for a worthwhile charity, project, or cause. Cause related marketing creates a mutually profitable outcome for the business and charity. Cause marketing can be a highly effective method that contributes to building a positive image for the business, while helping a charity gain much needed visibility.